Finite-element Adaptive Meshing Statistics of Liquid Crystal Coaxial Phase Shifters for mmW Electronics and THz Photonics Beyond Display: A Comparative Study - Li, Jinfeng; Li, Haorong (Photonics Letters of Poland, 2024)
Sub-mmW and THz frequencies offer ultra-high-speed communications for next-generation 5G/6G networks, wherein research advancing the understanding will benefit the electronics and photonics community. Specifically, meshing resolutions across varying frequency ranges and material properties are central to the solution accuracy, reliability, and cost (memory and time) of computational mmW and THz simulations, particularly for the emerging reconfigurable coaxial phase shifters employing nematic liquid crystals (LCs) as tunable media. In the present study, a comparative meshing statistics analysis is conducted for two devices designed for 60 GHz and 0.3 THz, respectively. Each design features two distinct tuning states (LC permittivity of 2.754 and 3.3, respectively), all pertinent to the coaxial TEM (Transverse Electromagnetic) mode. By quantifying the broadband meshing and solution statistics of diverse frequencies and dielectric tuning states for the first time, we establish memory-conserving computational metrology involving reconfigurable coaxial devices operationalized with LC-filled tunable dielectrics tailored for mmW electronics and THz photonics. Full Text: PDF References M. Makowski, I. Ducin, K. Kakarenko, J. Suszek, A. Kowalczyk, "Performance of the 4k phase-only spatial light modulator in image projection by computer-generated holography", Phot. Lett. Poland 8, 1 (2016). CrossRef J.F. Li, H.R. Li, "Liquid Crystal-Filled 60 GHz Coaxially Structured Phase Shifter Design and Simulation with Enhanced Figure of Merit by Novel Permittivity-Dependent Impedance Matching", Electronics 13, 3 (2024). CrossRef J.F. Li, H.R. Li, "Modeling 0.3 THz Coaxial Single-Mode Phase Shifter Designs in Liquid Crystals with Constitutive Loss Quantifications", Crystals 14, 4 (2024). CrossRef J.F. Li, D.P. Chu, "Liquid Crystal-Based Enclosed Coplanar Waveguide Phase Shifter for 54–66 GHz Applications", Crystals 9, 12 (2019). CrossRef Z. Cendes, "The development of HFSS", USNC-URSI Radio Science Meeting (Fajardo, IEEE 2016). CrossRef T. Vaupel, "Accuracy And Modeling Improvements For An Integral Equation Framework Applied To Thin Layer Microstrip And Substrate Integrated Waveguide (Siw) Structures", EuCAP (Copenhagen, IEEE 2020). CrossRef L.J. Jiang, W.C. Chew, "Low-frequency fast inhomogeneous plane-wave algorithm (LF-FIPWA)", Microwave Opt. Tech. Lett. 40, 2 (2004). CrossRef J. Zhu, D. Jiao, "Eliminating the Low-Frequency Breakdown Problem in 3-D Full-Wave Finite-Element-Based Analysis of Integrated Circuits", IEEE Trans. Microw. Theory Tech. 58, 10 (2010). CrossRef